The Rezort (2015): Zombies, Refugees and B Protocols - Audissino, Emilio (Cinémas, 2024)
The Rezort (Steve Barker, 2015) tells the story of a post-zombie-apocalypse U.K. in which the remaining specimens of the zombie population are employed as attractions at “The Rezort,” a leisure island on which humans can have zombie-theme safari experiences, including remorseless shooting of the undead. The apparently formulaic narrative comes with an ambitious social commentary. The film directly links zombies, and their exploitative and persecutory treatment, to refugees, reflecting the worries of public opinion in the U.K. around the migration crisis at the time of its production. The article offers textual analysis inspired by the four levels of meaning (referential, explicit, implicit, symptomatic) found in David Bordwell’s Making Meaning (1989). The eye-match dynamics are analyzed as textual cues for the creation of the explicit meaning (zombies are people too), and the narrative turning point and holocaust references are interpreted as cues to the implicit meaning (the refugee crisis is like previous persecutions in history). Finally, cues in the film are interpreted as symptoms of the impending Brexit, the referendum for which would take place the year after the film’s release.